Generation change in Russian poetry of the 19th and 20th centuries: a case study in comparative textual analyses: «Смена поколений» в русской поэзии XIX и ХХ вв.: опыт сравнительного текстологического анализа - Kotin, Michaił L. (Przegląd Wschodnioeuropejski, 2020)
The paper attempts to provide an analyses of poetically-encoded discourse about generation change in selected verses written by outstanding Russian poets of the 19th and 20th century – Pushkin, Zhukovsky, Baratynsky, Esenin and Mayakovsky, under a partial comparison with similar motives appearing by the German poet Goethe. The central problem is the axiological assessment of continuity vs. conflict of generations as well as the general confrontation with the “challenge of time”, both from existential and socially determined perspectives. The concepts of positive vs. negative connoted changes and the problem of their acceptability in the analysed verses are presented by means of a formal-semantic description with a special stress on language entities denoting the conceptual sphere of time and generation change.